(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2012)
A protocol was established for in vitro shoot proliferation and plant regeneration of a rare medicinal shrub of Bangladesh, Plumbago indica L. (Plumbaginaceae) using shoot tip and nodal explants. Best shoot induction was observed on MS medium supplemented with 0.5 mg/l BAP, in which 92% of nodal explants responded to produce maximum number (42.8 ± 1.18) of shoots per explants. In vitro raised shoots rooted on half strength of MS medium with 0.5 mg/l IAA. For acclimatization and transplantation, the plantlets in the rooting culture tubes were kept in normal room temperature for 7 days before transplanting them in pots containing soil where plantlets were reared for three weeks. The survival rate of regenerated plantlets was 82%. DOI: http://dx.doi.org/10.3329/bjsir.v47i2.11452 Bangladesh J. Sci. Ind. Res. 47(2), 197-202, 2012